Elemental mercury injection into the hand: A case report - Katare, Rajendra Kumar; N, Shalini; Patil, Manajeet (Indian Journal of Case Reports, 2019)
Injecting mercury for suicidal purposes is very uncommon and only a few cases have been reported. Here, we present an unusual case of injection of elementalmercury into the hand by a 27-year-old male leading to cellulitis. The need for debridement and chelation therapy based on the measured blood and urine mercury levels has been discussed.